PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PADA INDUSTRI PULP AND PAPER YANG TERDAFTAR DI BURSA EFEK INDONESIA - Shafwati "; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose this study was to determine the effect of working capital management toprofitability in industry pulp and paper listed in Indonesia Stock Exchange. Variables ofworking capital indicated by working capital turnover and profitability was indicated byReturn on Investment (ROI).The data used were taken from financial statements of each company obtained fromIDX which is located at Jenderal Sudirman street number 73 pekanbaru. The population inthis study is pulp and paper companies listed in Indonesia Stock Exchange. Method that wasused to pick the samples is purposive sampling and obtained a samples of 6 companies havefinancial statements period 2008-2012, so that obtained of 30 observation.The data analysis technique used is simple linear regression. SPSS 17 is the softwarewhich was used to analysis the data in this research. The result of analysis indicate thatworking capital turn over have no significant effect on Return on Investmen (ROI).Keywords : Working Capital, Profitability, Working Capital Turn Over, ROI